Helping children with aggression and conduct problems : best practices for intervention - Bloomquist, Michael L.; Schnell, Steven V. (New York : Guilford Press, 2002)
Offers empirically supported guidelines for delivering effective services to three- to twelve-year-olds with aggression and conduct problems and includes best practices for assessment and intervention planning, child and parent/family skills building, mental health treatments, school-based interventions, and community-based child and family support.
Reprint. Originally published: 2002.
Includes bibliographical references and index.
Keywords: Aggression; Child; Social Behavior Disorders; Violence